Changing Museums Through Cooperation and Collaboration. (2nd January 2021) - Kampschulte, Lorenz; Hatcher, Sarah Junk
ABSTRACT: Working within a new museological paradigm that sees museums as fluid, unbounded, and dependent upon context, this article seeks to examine the discourses that underpin collaboration as a contemporary and necessary museum education practice. In conducting this examination we will use examples from both Germany and the United States to illustrate the fact that though the two nations exist thousands of miles apart, and the museums within each nation are situated in different socio-political and cultural contexts, the underlying purpose of collaboration is the same in each nation and its museums. Collaboration seeks to change the museum from, in the immortal words of Stephen Weil, being about something to being for somebody.